1984
DOI: 10.1016/0009-8981(84)90076-7
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric complexes and fragments of albumin in normal human plasma

Abstract: Nitrocellulose blots of normal human plasma proteins separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis were examined for polymeric complexes and fragments of albumin using an immunoperoxidase-labelled mouse monoclonal anti-human albumin antibody. Under reducing conditions, no polymeric complexes were seen. Under non-reducing conditions, polymeric complexes were detected at the following molecular weights: 210 000, 168 000, 147 000, 132 000, and 110 000. These probably represent both homo- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…This finding is in agreement with previous studies that identified small amounts (,2%) of LMW albumin fragments in normal human plasma. 22 Up to 5% of albumin was found in a fragmented form in plasma samples from nephrotic syndrome patients. 11 Other reports have, by mass spectrometry analysis, further identified albumin fragments in normal plasma 23,24 as well as plasma of patients with focal segmental glomerulosclerosis, 25 uremia, 26 and diabetes.…”
mentioning
confidence: 99%
“…This finding is in agreement with previous studies that identified small amounts (,2%) of LMW albumin fragments in normal human plasma. 22 Up to 5% of albumin was found in a fragmented form in plasma samples from nephrotic syndrome patients. 11 Other reports have, by mass spectrometry analysis, further identified albumin fragments in normal plasma 23,24 as well as plasma of patients with focal segmental glomerulosclerosis, 25 uremia, 26 and diabetes.…”
mentioning
confidence: 99%
“…In a study performed to investigate whether plasma of healthy subjects contains albumin dimers, researchers found that the circulation contained not only small amounts of dimers and polymers in addition to albumin monomers, but also small amounts of albumin fragments [20]. In a subsequent study, researchers found that urine of proteinuric patients contains even greater amounts of albumin fragments in addition to albumin dimers [21].…”
Section: Albumin Fragmentsmentioning
confidence: 96%
“…In this study, we found that albumin fragments (AF) were fragmented by 2-mercaptoethanol and SDS treatment of modified human albumin. Wiggins et al (5) have already reported that both fragmentation and polymerization of albumin in urine occur not only in nephrotic patients, but also in healthy humans, and UAFappears about two-fifths of the way along the polypeptide chain to yield fragments with molecular weights of about 45kD and 30kD (5,6). Wealso confirmed that AF existed in blood obtained from diabetic patients, patients with other diseases and healthy volunteers, but it was assumed that no proteases acted in the urine because wecould hardly detect any UAFin healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been found that an increased thickness of the glomerular basement membrane, a higher fractional volume of the mesangium, and higher mesangial volume per glomerulus are observed in diabetic patients with microalbuminuria (4). Urinary albumin fragments were first reported by Wiggins and his colleagues (5), who noted that albumin fragments are found in plasma and urine, but they did not refer to any relation with diabetes mellitus (5,6). The aim of the present study was to analyze urinary albumin fragments (UAF) as a new clinical parameter to predict the development of diabetic nephropathy before the emergence of microalbuminuria.…”
Section: Introductionmentioning
confidence: 99%